Climate-driven reduction in biomass production of the Eurasian steppe coincides with nomadic migration during the first millennium CE - Feng Chen; Xiaoen Zhao; Weipeng Yue; Shijie Wang; Yong Zhang; Youping Chen; Mao Hu; Jan Esper; Ulf Büntgen; Fredrik Charpentier Ljungqvist; Amy E. Hessl; Max C. A. Torbenson; et al. (Proceedings of the National Academy of Sciences, 2026)
Although it is generally accepted today that climate and other environmental factors affected past human societies at different spatiotemporal scales, direct linkages are difficult to determine, and correlation should not be confused with causation. Here, we use a tree-ring width network of multimillennial chronologies from inner Eurasia to reconstruct annual changes in Net Primary Productivity (NPP) back to 200 BCE. Our findings reveal that episodes of reduced NPP around the 70s–100s, 360s–380s, and 470s–560s CE likely contributed to the westward and southward migration of nomadic people from their homelands in northwestern China and Mongolia. Although prolonged multidecadal periods of climate-induced low NPP served as tipping points for agricultural and pastoral subsistence systems, the inherent mobility of nomadic communities not only enabled them to adapt to adverse environmental conditions but also facilitated a widespread dispersal of ethnic groups.